Backyard bears : conservation, habitat changes, and the rise of urban wildlife - Cherrix, Amy E. (Scientists in the field., 2018)
Examines the concerns surrounding the current population of black bears living within the city of Asheville, North Carolina. Offers tips for how to be safe living around black bears and what to do if you encounter one face-to-face. Includes maps, a glossary, resources for further information, and color photographs.